PENGARUH KEBERAGAMAN MENU TERHADAP KEPUASAN KONSUMEN PADA HOTEL ASTON KUPANG - Friend Zakharia (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2023)
Hotel Aston Kupang is a four-star hotel with 179 rooms on 18 floors that is responsible for all the quality of services offered including menu diversity that makes guests satisfied. In this study using descriptive statistical research methods and inferential statistics with 80 respondents by determining the number of samples using simple random sampling techniques. Data collection techniques using questionnaires, observations, irregular interviews and literature studies. This research uses data analysis techniques including: validity test, reliability test, simple linear regression test and the coefficient of determination. Based on simple linear regression analysis, the t value of 4.189 is more than t table 1.679, indicating that menu diversity has an effect on consumer satisfaction. The coefficient results obtained r squared value of 0.34 which means the effect of menu diversity on customer satisfaction at the Aston Kupang hotel is 34%.